Evaluating the operation and routine maintenance of municipal roads in Switzerland. Issue 3 (9th June 2017) - Adey, Bryan T; García de Soto, Borja; Senn, Christian
Abstract : Evaluating the performance of road managers in terms of the operation and routine maintenance of roads is not possible without data. As road managers are increasingly using computerised management systems, however, there is an increasing amount of data available. With this in mind, a project was conducted to determine the extent with which currently available data could be used for this purpose in Switzerland. This paper contains an explanation of the methodology used in, and the main results of, this project. The methodology used includes ( a ) the clarification of terminology, ( b ) the identification of the possible indicators, ( c ) the collection of data, ( d ) the identification of the base and advanced key indicators, ( e ) the investigation of modification factors to be used to compare different municipal road managers and ( f ) the investigation of economies of scale. It is concluded that it is possible with the available data to obtain an idea of the performance of road managers in Switzerland with respect to both operation and routine maintenance. The results give indications of whether or not road managers are spending too much or too little, why this might be happening and how much improvement they can expect if changes are made.